2021
DOI: 10.4103/njcp.njcp_398_20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prosthetic Framework Material, Cantilever Length and Opposing Arch on Peri-Implant Strain in an All-on-Four Implant Prostheses

Abstract: Aim: To evaluate the effect of prosthetic framework material and cantilever length on peri-implant strain in mandibular all-on-four implant-supported prostheses with different types of arch antagonist forces. Materials and Methods: Models simulating a completely edentulous mandibular arch fabricated in heat-cured acrylic resin were used. On the acrylic models, four implants were placed at regions 34, 32, 42, and 44 simulating all-on-four implant placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Shetty and colleagues 58 demonstrated that natural teeth were sensitive to even a very small occlusal force and could recognize the discrimination of its direction and magnitude, wherein the enamel‐dentine‐pulp complex and the mechanoreceptors on the periodontal ligament of the natural teeth formed the peripheral feedback system, which the implants lacked. The overload on the implants was usually not easily and timely perceived, thus becoming a common risk factor for implant's MBL 59 …”
Section: Discussionmentioning
confidence: 99%
“…Shetty and colleagues 58 demonstrated that natural teeth were sensitive to even a very small occlusal force and could recognize the discrimination of its direction and magnitude, wherein the enamel‐dentine‐pulp complex and the mechanoreceptors on the periodontal ligament of the natural teeth formed the peripheral feedback system, which the implants lacked. The overload on the implants was usually not easily and timely perceived, thus becoming a common risk factor for implant's MBL 59 …”
Section: Discussionmentioning
confidence: 99%
“…The All-on-4 concept originated in 1999, with Mattsson and colleagues treating severely resorbed edentulous maxillae by placing four to six implants in the premaxilla to avoid sinus augmentation [ 13 ]. In challenging clinical circumstances involving inadequate bone volume and the need for bone grafting in fully edentulous patients, the use of angled implants in the All-on-4 approach provides a viable treatment option, offering excellent long-term results and better load distribution [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prosthetic materials may play an important role in the stresses induced at implant/bone interface [30,31] .…”
Section: Discussionmentioning
confidence: 99%